Pengaruh Disiplin Kerja dan Komunikasi terhadap Kinerja Pegawai PT Sumatera Inti Karet Marindal - Haya, Aqilla Fadia; Tarigan, Nur M. Ridha; Nasution, Ismail (JRMB (Jurnal Riset Manajemen & Bisnis), 2024)
This study aims to analyze the influence of work discipline and communication partially and simultaneously on the performance of employees work in the PT. Sumatera Inti Karet Marindal. PT. Sumatera Inti Karet Marindal Jalan Roso Melati 5 Dusun 8 Marindal 1, Kabupaten Deli Serdang, Provinis Sumatera Utara, with a population of 101 people, and a study sample of 50 people. Based on the analysis results obtained work discipline have a positive and significant effect on the performance of employees work of the PT. Sumatera Inti Karet Marindal, this is supported by the results of t count analysis t-table (3,529 2,012) Communication has a positif and significant effect on the performance of employees work of the PT. Sumatera Inti Karet Marindal, this is supported by an analysis of t count t-table (4,190 2,012).Value of F-count F table (27,171 3,20) This states that together (multiple) there are positive and significant effects of work discipline andcommunication on the performance of employees work of employees of the PT. Sumatera Inti Karet Marindal. Thus the hypothesis proposed is accepted by the truth.